1980
DOI: 10.1111/j.1471-4159.1980.tb11177.x
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro Synthesis of RNA within the Rat Nodose Ganglion Following Vagotomy

Abstract: This report describes the application of an in vitro labelling procedure for the evaluation of changes in the uptake and incorporation of tritiated nucleotides into RNA of the rat nodose ganglion following crush injury of the cervical vagus nerve. Significant changes in the incorporation into 28S, 18S and 4S RNA were observed at 3 and 9 days after injury which confirms and extends our previous in vivo observations where [32P]orthophosphate was used as the precursor. An early stimulation in the uptake of nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In both the axotomy and hormone-treated series, a transition point at the end of the first postoperative week was observed. The presence of two phases of the axon reaction has been documented by others, principally with regard to RNA synthesis (Langford et al, 1980;Austin et al, 1983;Wells, 1984Wells, , 1987. The significance of these two phases is unclear; however, it may be that the early phase represents events associated with generalized cellular stress, and the later phase represents events focused on rebuilding the severed axon.…”
Section: Discussionmentioning
confidence: 88%
“…In both the axotomy and hormone-treated series, a transition point at the end of the first postoperative week was observed. The presence of two phases of the axon reaction has been documented by others, principally with regard to RNA synthesis (Langford et al, 1980;Austin et al, 1983;Wells, 1984Wells, , 1987. The significance of these two phases is unclear; however, it may be that the early phase represents events associated with generalized cellular stress, and the later phase represents events focused on rebuilding the severed axon.…”
Section: Discussionmentioning
confidence: 88%
“…Increased mRNA synthesis has been observed in sensory neurons following axotomy (Barron 1989;Langford et al 1980;Wells 1987). We have recently developed in situ hybridization methods using subtype-specific riboprobes that permit the analysis of sodium channel mRNA expression in identified cells (Black et al 1994a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The redirection of protein synthesis in the neuron during chromatolysis ultimately is under the control of the nucleus. In attempting to discover more precisely the possible locus of this control, past studies in this laboratory have concentrated on the early changes in metabolism of various forms in RNA following nerve injury (Gunning et al, 1977a,b;Langford et al, 1980;Moses et al, 1982). These studies revealed both qualitative and quantitative changes in RNA synthesized in the ganglia of nodose and sympathetic nerves following axotomy.…”
mentioning
confidence: 99%